Changes of Fat Volume and Adipocytokines by the Randomized Intervention Program for Obesity Control Program (SCOP) - Nobuhisa Kawashima; Shaw Watanabe; Akemi Morita; Naomi Aiba; Motohiko Miyachi5 (Diabetes Research, 2016)
Adipocytokines are bioactive substances synthesized and secreted by fat cell. Previous studies have reported an association between weight loss and adipocytokines. However, these studies are inconsistent and they have not clarified the relationship between weight regain and changes in circulating levels of adipocytokines. In this study, we analyzed the relationship between weight and fat volume changes and adipocytokines. The subjects were 235 obese people recruited in the Saku Control Obesity Program (SCOP). Participants were randomly assigned to either immediate (Group A) or delayed (Group B, control group). Group A participants were followed for another two years after completion of the one year intervention. As controls, Group B participants received the same intervention as Group A after a delay of one year. Then they were followed up for one year. The intervention consisted in a one-year lifestyle program to induce weight loss, based on a cognitive-behavioral approach. After the first year of the study, body weight, Body Mass Index (BMI), body fat and abdominal fat areas were significantly lower in group A participants, compared to controls. After the intervention, leptin levels were significantly lowered both in men and women. After one year follow-up, both men and women re-gained about 1.5 kg body weights on average. BMI, waist circumference, fat areas by Computed Tomography (CT) and Glycated hemoglobin (HBA1c) significantly increased during the follow-up period. The change of adipocytokine levels by analysis of the quartile of body weight decrease and regain revealed that increased adiponectin and decreased leptin was noteworthy for weight reduction, while increase of leptin influenced the weight regain. In conclusion, our results suggest that leptin could have broad effects on the distribution of fat tissues and on lipid metabolism. Leptin inversely associated with adiponectin, which in turn was necessary to decrease body weight. In particular, leptin decreased remarkably in the process of weight reduction, and its increase seemed to be related in weight regain. The observed increase of adiponectin seemed to be induced by reduction in fat volume.